A 150 kDa plasma membrane complex of AtNRT2.5 and AtNAR2.1 is the major contributor to constitutive high‐affinity nitrate influx in Arabidopsis thaliana. (31st January 2015) - KOTUR, ZORICA; GLASS, ANTHONY D. M.
Abstract In plants that have been deprived of nitrate for a significant length of time, a constitutive high‐affinity nitrate transport system (cHATS) is responsible for initial nitrate uptake. This absorbed nitrate leads to the induction of the major nitrate transporters and enzymes involved in nitrate assimilation. By use of 13NO3– influx measurements and Blue Native polyacrylamide gel electrophoresis we examined the role of AtNRT2.5 in cHATS in wild type (WT) and various T‐DNA mutants of Arabidopsis thaliana. We demonstrate that AtNRT2.5 is predominantly expressed in roots of nitrate‐deprived WT plants as a 150 kDa molecular complex with AtNAR2.1. This complex represents the major contributor to cHATS influx, which is reduced by 63% compared with WT in roots of Atnrt2.5 mutants. The remaining cHATS nitrate influx in these mutants is due to a residual contribution by the inducible high‐affinity transporter encoded by AtNRT2.1/AtNAR2.1. Estimates of the kinetic properties of the NRT2.5 transporter reveal that its low Km for nitrate makes this transporter ideally suited to detect and respond to trace quantities of nitrate in the root environment.